Refining the pathovar paradigm via phylogenomics of the attaching and effacing Escherichia coli - Hazen, Tracy H; Sahl, Jason W; Fraser, Claire M; Donnenberg, Michael S; Scheutz, Flemming; Rasko, David A (Proceedings of the National Academy of Sciences - PNAS, 2013)
The attaching and effacing Escherichia coli (AEEC) are characterized by the presence of a type III secretion system encoded by the locus of enterocyte effacement (LEE). Enterohemorrhagic E. coli (EHEC) are often identified as isolates that are LEE+ and carry the Shiga toxin (stx)-encoding phage, which are labeled Shiga toxin-producing E. coli; whereas enteropathogenic E. coli (EPEC) are LEE+ and often carry the EPEC adherence factor plasmid-encoded bundle-forming pilus (bfp) genes. All other LEE+/bfp-/stx- isolates have been historically designated atypical EPEC. These groups have been defined based on the presence or absence of a limited number of virulence factors, many of which are encoded on mobile elements. This study describes the comparative analysis of the genomes of 114 LEE+ E. coli isolates. Based on a whole-genome phylogeny and analysis of type III secretion system effectors, the AEEC are divided into five distinct genomic lineages. The LEE+/stx+/bfp- genomes were primarily divided into two genomic lineages, the O157/O55 EHEC1 and non-O157 EHEC2. The LEE+/bfp+/stx- AEEC isolates sequenced in this study separated into the EPEC1, EPEC2, and EPEC4 genomic lineages. A multiplex PCR assay for identification of each of these AEEC genomic lineages was developed. Of the 114 AEEC genomes analyzed, 31 LEE+ isolates were not in any of the known AEEC lineages and thus represent unclassified AEEC that in most cases are more similar to other E. coli pathovars than to text modification AEEC. Our findings demonstrate evolutionary relationships among diverse AEEC pathogens and the utility of phylogenomics for lineage-specific identification of AEEC clinical isolates.